Synthesis and Identification of Biaryi of Cholic Acid Derivatives via Suzuki-Miyaura Cross-coupling Reaction and Study of Their Biological Activity - Abbas Sami Abd (Journal of Global Pharma Technology, 2018)
Cholic acid derivatives(2-6) and (10-15)were Synthesized by treatment of cholic acid 1 with 4-aminoaniline  in the presence of N, N'- Dicyclohexylcarbodiimide (DCC) as coupling reagent and 4-dimethylaminopyridine (DMAP) as catalyst in CH2Cl2-DMF gave compound (2) that reacted with approperate cyanophenyl, 2,3-diflurophenyl, 3,4-dimethoxy phenyl)boronic acid using palladium (0) tetraks - triphenyl phosphine (Pd(0)Ph3P)4) and Na2CO3 as a catalysts in 2ml from DMF and H2O by using microwave Technique afford (10-12)  . The carbohydrazide derivative (5, 6) was prepared from methyl cholate 3 and hydrazine hydrate. The prepared hydrazone was introduced by reaction of the cholic acid with the carbonyl compounds (4-formyl phenyl boronic acid and 4-bromo ace to phenone) in refluxing acidic Et OH. The synthesis of compounds (14-15)  was accomplished from (6) with appropriately functionalized boronic acid derivatives by using Susuki - Miyaura criss-coupling reaction while the compounds(13) synthesized from reaction of (5) with (6) under Susuki - Miyaura criss-coupling reaction too (.some of these compounds show moderate to good  activity against Staphylococcus aureus bacteria and Candida albicans fungal. The reaction was monitored by (TLC) technique. All new Cholic acid derivatives were characterized by melting points, elemental analysis, FT‐ Invra red radiation, 1H, 13C spectroscopy. Antimicrobial activity of these derivatives was also determined.Keywords: Cholic acid, Cholic acid hydrazones ,Bile acids, Susuki -Miyaura cross -coupling reaction, Antimicrobial activity.